OP0061 Diffuse alveolar hemorrhage: a multicenter study in 847 childhood-onset systemic lupus erythematosus patients. (15th June 2017) - Silva, CA; Blay, G; Rodrigues, JC; Leal, GN; Ferreira, JC; Novak, G; Pereira, RMR; Terreri, MT; Magalhães, CS; Molinari, BC; Sakamoto, AP; Aikawa, NE; et al.
Abstract : Background: Data of diffuse alveolar hemorrhage (DAH) in childhood-onset systemic lupus erythematosus (cSLE) patients are limited due to the small representation of this complication in previous case series or the focus on the comparison to adult SLE, precluding an accurate analysis of associated factors and outcomes in patients with and without this severe complication. Objectives: To evaluate prevalence, clinical manifestations, laboratory abnormalities and treatment in a multicenter cohort study including 847 cSLE patients with and without diffuse DAH, as well as concomitant parameters of severity. Methods: DAH was defined as the presence of at least three respiratory symptoms or signs associated with diffuse interstitial/alveolar infiltrates on chest x-ray or high-resolution computer tomography and sudden drop in hemoglobin levels with no other source of bleeding. Holm-Bonferroni correction for multiple comparisons was performed adjusting the significance level (p<0.0022). Results: DAH was evidenced in 19/847 (2.2%) cSLE patients. Cough/dyspnea/tachycardia/hypoxemia occurred in all cSLE patients with DAH. Concomitant parameters of severity observed were: mechanical ventilation in 14/19 (74%), hemoptysis 12/19 (63%), macrophage activation syndrome 2/19 (10%) and death 9/19 (47%). Further analysis of cSLE patients at DAH diagnosis compared to 76 cSLE control patients without DAH with same disease duration [3 (1–151) vs. 4 (1–151) months, p=0.335], showed higher frequencies of constitutional involvement (74% vs. 10%, p<0.0001), serositis (63% vs. 6%, p<0.0001) and sepsis (53% vs. 9%, p<0.0001) in the DAH group. The median of disease activity score (SLEDAI-2K) was significantly higher in cSLE patients with DAH [18 (5–40) vs. 6 (0–44), p<0.0001]. The frequencies of thrombocytopenia (53% vs. 12%, p<0.0001), intravenous methylprednisolone (95% vs. 16%, p<0.0001) and intravenous cyclophosphamide (47% vs. 8%, p<0.0001) were also significantly higher in DAH patients. Conclusions: This is the largest study to evaluate DAH. This complication, although not a disease activity score descriptor, occurs in the context of significant moderate/severe cSLE flare. Importantly, we identified that this condition is associated with serious disease flare complicated by sepsis and with high mortality rate. Acknowledgements: This study was supported by research grants from Conselho Nacional de Desenvolvimento Científico e Tecnolόgico (CNPq 301805/2013-0 to RMRP, 303752/2015-7 to MTT, 301479/2015-1 to CSM, 305068/2014-8 to EB and 303422/2015-7 to CAS), Federico Foundation (to EB, RMRP and CAS) and by Núcleo de Apoio à Pesquisa "Saúde da Criança e do Adolescente" da USP (NAP-CriAd) to CAS. Disclosure of Interest: : None declared